Morphological and phenotypical characteristics of porcine satellite glial cells of the dorsal root ganglia - Zdora, Isabel; Jubran, Lorna; Allnoch, Lisa; Hansmann, Florian; Baumgärtner, Wolfgang; Leitzen, Eva (Frontiers in Neuroanatomy, 2022)
Satellite glial cells (SGCs) of the dorsal root ganglia (DRG) ensure homeostasis and proportional excitability of sensory neurons and gained interest in the field of development and maintenance of neuropathic pain. Pigs represent a suitable species for translational medicine with a more similar anatomy and physiology to humans compared to rodents, and are used in research regarding treatment of neuropathic pain. Knowledge of anatomical and physiological features of porcine SGCs is prerequisite for interpreting potential alterations. However, state of knowledge is still limited. In the present study, light microscopy, ultrastructural analysis and immunofluorescence staining was performed. SGCs tightly surround DRG neurons with little vascularized connective tissue between SGC-neuron units, containing, among others, axons and Schwann cells. DRG were mainly composed of large sized neurons ( 59%), accompanied by fewer medium sized ( 36%) and small sized sensory neurons ( 6%). An increase of neuronal body size was concomitant with an increased number of surrounding SGCs. The majority of porcine SGCs expressed glutamine synthetase and inwardly rectifying potassium channel Kir 4.1, known as SGC-specific markers in other species. Similar to canine SGCs, marked numbers of porcine SGCs were immunopositive for glial fibrillary acidic protein, 2',3'-cyclic-nucleotide 3'-phosphodiesterase and the transcription factor Sox2. Low to moderate numbers of SGCs showed aquaporin 4-immunoreactivity as described for murine SGCs. AQP4-immunoreactivity was primarily found in SGCs ensheathing small and medium sized neuronal somata. Low numbers of SGCs were immunopositive for ionized calcium-binding adapter molecule 1, indicating a potential immune cell character. No immunoreactivity for common leukocyte antigen CD45 nor